Freemasonry as the Nucleus of the Human League—Karl Christian Friedrich Krause’s Interpretation of Regular Freemasonry as a Precursor of a Cosmopolitan Civil Society - Benedikt Paul Göcke (Religions)
In the spirit of global governance, Karl Christian Friedrich Krause saw the Masonic Brotherhood as the first historical seed for the realization of a global, participatory, Human League; to establish and maintain a state of true humanity. And he saw the most excellent sign of this connection between Freemasonry and cosmopolitan civil society in the allegory of the “Great General Lodge”. However, in order to be able to do justice to its historical task of establishing the Human League, according to Krause, Freemasonry needs to reform itself according to its original ideal, overcome its pupal stage caused by the caterpillar status of medieval construction huts, and grow into a butterfly.